Prophylactic internal iliac artery balloon occlusion in the management of placenta accreta spectrum disorders: a meta-analysis - Nicole dos Santos Pimenta; Ana Clara Felix de Farias Santos; Maírla Marina Ferreira Dias; Gabriela Oliveira Gonçalves Molino; Ana Gabriela Alves Pereira; Pedro Henrique Costa Matos da Silva (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Placenta accreta spectrum (PAS) describes the failure of placental detachment. PAS is a pregnancy-associated life-threatening condition which increases hemorrhage risk. We evaluated safety and efficacy of internal iliac artery balloon occlusion (IIABOC) on bleeding volume among pregnant women with diagnosis or suspicion of PAS. Data source: We searched PubMed, Embase and Cochrane databases. Study selection: Randomized controlled trials (RCTs) and observational studies comparing the efficacy of preoperative prophylactic balloon catheters to a control group with standard care in patients with a prenatal screening of PAS. Data collect: We computed odds ratio (OR) for binary endpoints and mean difference (MD) for continuous endpoints, with 95% confidence intervals (CIs). We performed random effects models and assessed I2 heterogeneity statistics. Data synthesis: Twenty-four studies were included, of whom 1,023 (51%) received balloons and 983 (49%) did not undergo balloon management. Patients receiving IIABOC had a greater decrease in estimated blood loss (MD −0.33; 95% CI −0.55, 0.11) and increase in operation time (MD 17.21; 95% CI 3.43, 30.99). Apgar score at fifth minute (MD −0.22; 95% CI −0.36,−0.07) significantly decreased. There were no significant differences between groups regarding hysterectomy rates (OR 1.35; 95% CI 0.88, 2.09) and maternal intensive care unit admission (OR 0.81; 95% CI 0.51,1.29). Conclusion: While IIABOC have demonstrated a significant reduction in estimated blood loss, these findings have not been consistently replicated in RCTs and the surgeon's level of experience must be taken into account since it biases the analysis.